1988
DOI: 10.1063/1.454642
|View full text |Cite
|
Sign up to set email alerts
|

Intermultiplet and angular momentum transfers of excited sodium atoms in collisions with molecules. I. Experiment

Abstract: Intermultiplet and angular momentum transfers of excited sodium atoms in collisions with molecules. II. Models

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Na[3P] has enough energy to populate the first 3 vibrational levels of H 2 and a subsequent reaction of the vibrationally excited hydrogen with other Na[3P] atoms can form NaH: Na[3P] + H 2 (ν ≥1) → NaH + H, with a rate of 1.1×10 −9 cm −3 s −1 (Motzkus et al 1998). Deactivation of Na[4P] state to the Na[3D] state was found to proceed with a cross section of 7Å 2 at 700 K (Astruc et al 1988), and deactivation of Na[4S] was observed to dominantly quench to Na[3P] with a cross section of 41.4Å 2 (Astruc et al 1986). In later studies, Kleiber et al (1993) found that the reactive and non-reactive quenching channels in the collision of Na[4P] with H 2 (at 470 K) proceed with a ratio of ∼1 and a total cross sections of ∼18Å 2 .…”
Section: Excited State Chemistrymentioning
confidence: 99%
“…Na[3P] has enough energy to populate the first 3 vibrational levels of H 2 and a subsequent reaction of the vibrationally excited hydrogen with other Na[3P] atoms can form NaH: Na[3P] + H 2 (ν ≥1) → NaH + H, with a rate of 1.1×10 −9 cm −3 s −1 (Motzkus et al 1998). Deactivation of Na[4P] state to the Na[3D] state was found to proceed with a cross section of 7Å 2 at 700 K (Astruc et al 1988), and deactivation of Na[4S] was observed to dominantly quench to Na[3P] with a cross section of 41.4Å 2 (Astruc et al 1986). In later studies, Kleiber et al (1993) found that the reactive and non-reactive quenching channels in the collision of Na[4P] with H 2 (at 470 K) proceed with a ratio of ∼1 and a total cross sections of ∼18Å 2 .…”
Section: Excited State Chemistrymentioning
confidence: 99%
“…1-4 For H 2 it has been shown in many cases that the nonreactive quenching cross section is significantly larger than those for rare-gas atoms due to the existence of additional energy transfer pathways. 5,6 Reactive collisions of alkali atoms with molecular hydrogen leading to the formation of metal hydride MH have been subjects of intensive research over the last two decades. [7][8][9][10] They represent the simplest three-body problems and have been a very useful testing ground for a nonadiabatic process and other dynamical models.…”
Section: Introductionmentioning
confidence: 99%
“…This is a result of the existence of additional energy transfer pathways. 5,6 The collisions of alkali atoms with molecular hydrogen leading to a nonreactive inelastic scattering or a reactive collision leading to the formation of metal hydride have been subjects of intensive research over the last two decades. [7][8][9][10] They represent the simplest three-body problems and have been a very useful testing ground for a nonadiabatic process and other dynamical models.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in many cases that the nonreactive quenching cross section for H 2 is significantly larger than those for rare-gas atoms. This is a result of the existence of additional energy transfer pathways. , …”
Section: Introductionmentioning
confidence: 99%